Study to assess the role of bromocriptine in treatment of diabetes mellitus - Pathak, Anuj Kumar; Kumar, Subodh; Kumar, Manish; Dikshit, Harihar (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Bromocriptine is a dopamine D2 receptor agonist and a sympatholytic agent used very frequently in treatment of hyperprolactinemia, Parkinsonism and acromegaly. Its quick release formulation has been approved for treatment of type 2 diabetes mellitus as an adjunct to diet and exercise. This study evaluated the antihyperglycemic effect of quick release bromocriptine in alloxan induced diabetic rats. Methods: 24 albino rats were taken and divided into four groups of six rats in each group. Diabetes was induced in three groups and one group was kept as a control group. After successful induction of diabetes, in remaining three group, first group was given no treatment second group was treated with bromocriptine and the third group was treated with metformin. Fasting blood sugar of all the groups were measured on day 1, 7, 14 and 28 of treatment. Results: In this study both the treatment groups were found to have significant (P<0.05) antihyperglycemic effect. Further studies are needed to evaluate and compare antihyperglycemic effect and safety profile of bromocriptine with established antidiabetic drugs. Conclusions: From this study, we concluded that individually both metformin and bromocriptine were effective in controlling hyperglycemia but metformin was better in achieving normal mean FBS. Further studies are required to ascertain the consistency in hypoglycemic effect of bromocriptine as well as its effect in lipid profile and cardiovascular outcomes. Study taking different doses of bromocriptine or with increasing the duration of study can elaborate its role in achieving proper glycemic control over time.